Granulocytic anaplasmosis in three dogs from Saskatoon, Saskatchewan - Cockwill, Ken R. (Canadian Veterinary Medical Association, 2009)
Three dogs from Saskatoon, Saskatchewan were diagnosed with acute granulocytic anaplasmosis. Fever, lethargy, inappetence, vomiting, diarrhea, and lameness were reported. Lymphopenia, thrombocytopenia, and splenomegaly were identified in all dogs. Inclusions were identified within the cytoplasm of blood neutrophils, and infection with Anaplasma phagocytophilum was confirmed by polymerase chain reaction.